2011
DOI: 10.1007/s00726-011-1016-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the activation of recombinant microbial pro-transglutaminase: in contrast to proteinase K, dispase removes the histidine-tag

Abstract: In order to produce recombinant microbial transglutaminase (rMTG) which is free of the activating protease, dispase was used to activate the pro-rMTG followed by immobilized metal affinity chromatography (IMAC). As shown by MALDI-MS, the dispase does not only cleave the pro-sequence, but unfortunately also cleaves within the C-terminal histidine-tag. Hence, the active rMTG cannot properly bind to the IMAC material. As an alternative, proteinase K was investigated. This protease was successfully applied for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…ESI‐MS analysis of the synthetic construct 2 (Table S2) revealed that dispase cleaved 2 pro not only at its usual site, C ‐terminally from Ser in the SFRAP sequence, but also within the His 6 ‐tag sequence (see Supporting Information, section 2.3 and Figure S11). This observation corroborates previous data . Nonetheless, cells treated with either trypsin or enterokinase showed surface display of the enzyme and biotinylation, indicating that post‐display procession of pro‐mTG ( 4 pro and 5 pro , Table S2) succeeded (Figure b, middle and right panels).…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…ESI‐MS analysis of the synthetic construct 2 (Table S2) revealed that dispase cleaved 2 pro not only at its usual site, C ‐terminally from Ser in the SFRAP sequence, but also within the His 6 ‐tag sequence (see Supporting Information, section 2.3 and Figure S11). This observation corroborates previous data . Nonetheless, cells treated with either trypsin or enterokinase showed surface display of the enzyme and biotinylation, indicating that post‐display procession of pro‐mTG ( 4 pro and 5 pro , Table S2) succeeded (Figure b, middle and right panels).…”
Section: Figuresupporting
confidence: 91%
“…This observation corroborates previous data. [14] Nonetheless, cells treated with either trypsin or enterokinase showeds urface display of the enzyme and biotinylation, indicating that post-display procession of pro-mTG (4pro and 5pro,T able S2) succeeded (Figure 2b,m iddle and right panels).…”
mentioning
confidence: 94%
“…The S2P variant of rMTG from S. mobaraensis was expressed as Pro‐TG in E. coli BL21 in a histidine‐tagged form as described previously (Sommer et al ., ). After cell disruption and activation of Pro‐TG with Proteinase K the transglutaminase was purified by Ni‐IMAC (Sommer et al ., ). By the use of dialysis of active fractions against 50 m m Tris/HCl‐buffer, the TG precipitated.…”
Section: Methodsmentioning
confidence: 97%
“…Lyophilized monomers were solubilized in 50 m m Tris–HCl, pH 8.0 to a final concentration of 1 mg/mL. An equimolar solution of K‐MaSp1‐100xELP and Q‐MaSp1‐100xELP was treated with 0.5 U of rMTG (Sommer et al ., ) per μL protein solution at 11 °C with gentle shaking. The resulting cross‐linked ELPylated proteins were purified by cITC and desalted via gel filtration (Sephadex G‐50; Sigma‐Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Applications of TGases in material science require optimized enzymes, for instance with higher thermostability, as addressed by Büttner et al (2011) in this issue. These enzymes can be overproduced and purified on a mass scale as described by Sommer et al (2011).…”
mentioning
confidence: 99%